Implementasi Data Mining Menggunakan Algoritma C4.5 Dalam Mengukur Tingkat Kepuasan Pasien BPJS di RST. Dr. Reksodiwiryo - Febrianus (Jurnal Elektronika Listrik dan Teknologi Informasi Terapan, 2023)
The hospital institution is an institution engaged in the health sector. As an agency that serves public health, hospitals provide various facilities to serve patients. Therefore, patient needs are not only limited to receiving services from hospitals, but in order to improve the quality of service, hospitals must question patient opinions in getting attention and care. from the hospital. This research was conducted in an effort to measure the level of satisfaction of BPJS patients at RST. Dr. Reksodiwiryo by building a webstie system using the C4.5 data mining algorithm. this research will produce a system that can measure the level of satisfaction of BPJS patients so that the RST. Dr. Reksodiwiryo can improve the quality of service for BPJS patients.